2009
DOI: 10.1117/12.835088
|View full text |Cite
|
Sign up to set email alerts
|

LIF bio-aerosol threat triggers: then and now

Abstract: Bio-aerosol terrorist attacks have been carried out against civilians in the United States and elsewhere. Unfortunately, recurrence appears inevitable. A fast, reliable, and inexpensive bioaerosol threat detection trigger can be an important tool for detect-to-protect and detect-to-treat countermeasure scenarios. Bio-aerosol threat detection triggers employing light, historically laser light but recently LED light, for induced native-or auto-fluorescence (LIF) have been developed for well over a decade without… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…In parallel, the Naval Research Laboratory (NRL) demonstrated an elastic scatteringcued fluorescence sensor at 266 nm Seaver et al 1999). A collaboration between LL, NRL, and Edgewood Chemical and Biological Center led to an improved breadboard capability under the Rapid Agent Aerosol Detector (RAAD) program initiated in 2002 (DeFreez 2009;Jeys et al 2007) that employed an 808-nm structured beam as the cueing laser ), 355-nm polarized elastic scattering, dual fluorescence excitation at 266 and 355 nm (Sivaprakasam et al, 2004) that triggered laser-induced breakdown spectroscopy (Hybl et al 2006) at suspect events. The RAAD sensor was slated in 2017 to be the detector under the Enhanced Maritime Biological Detection (EMBD) program.…”
Section: Lif For Early Warning Of Human Pathogensmentioning
confidence: 99%
“…In parallel, the Naval Research Laboratory (NRL) demonstrated an elastic scatteringcued fluorescence sensor at 266 nm Seaver et al 1999). A collaboration between LL, NRL, and Edgewood Chemical and Biological Center led to an improved breadboard capability under the Rapid Agent Aerosol Detector (RAAD) program initiated in 2002 (DeFreez 2009;Jeys et al 2007) that employed an 808-nm structured beam as the cueing laser ), 355-nm polarized elastic scattering, dual fluorescence excitation at 266 and 355 nm (Sivaprakasam et al, 2004) that triggered laser-induced breakdown spectroscopy (Hybl et al 2006) at suspect events. The RAAD sensor was slated in 2017 to be the detector under the Enhanced Maritime Biological Detection (EMBD) program.…”
Section: Lif For Early Warning Of Human Pathogensmentioning
confidence: 99%
“…Technologies based on ultra-violet laser-induced fluorescence (UV-LIF) are capable of real-time, in situ detection and classification for biological and other organic carbon aerosols (e.g., [35][36][37][38], see a review by DeFreez [39]). A single-particle fluorescence spectrometer [SPFS, ref [38] can obtain the dispersed fluorescence spectra (280-700 nm) of individual airborne aerosol particles (1-10 lm size range) as they flow through the sensor.…”
Section: Introductionmentioning
confidence: 99%
“…The IBAC samples ambient air at 3 L/min and provides the total number concentrations for fluorescent particles (particle number per liter of air, particles/L) every second. The IBAC utilizes ultraviolet laser induced fluorescence (UV‐LIF) at an excitation wavelength of 405 nm to discriminate fluorescent particles from ambient background particles . The particles are binned into two size categories: 0.5‐1.7 and 1.7‐10 μm .…”
Section: Test Facility Study Design and Methodsmentioning
confidence: 99%